An integrated software system for microcomputer management of recombinant DNA data. - Campione-Piccardo, J (1986)
A database-oriented system (pCP123) is described for the manipulation of recombinant DNA data. This system was developed within the context of an integrated software package with spreadsheet, database, graphing and programming capabilities. The system includes two databases, one of sites and another of regions, coordinately handled by a series of macro-programs operated from four user-define menus. A distinctive feature of the system is the possibility of handling both ends of defined functional or structural regions in situations of simulated deletions or insertions.